Are patients satisfied with accessibility and services provided at siddha hospitals? Findings of patient satisfaction survey from a district of South India - D., Venkatachalam; Selvaraj, Kalaiselvi; Ramaswamy, Gomathi; A., Veerakumar; Chinnakali, Palanivel; Saya, Ganesh Kumar (International Journal Of Community Medicine And Public Health, 2018)
The study was aimed to assess patient satisfaction about with services provided by Siddha (indigenous) system of medicine which was merged with public health system recently in India. A facility based cross-sectional study was conducted among the outpatients attending selected siddha hospitals in Tamil Nadu. Perception regarding the quality of services was assessed from every 10th patient visiting the hospitals during the month of February and March 2014. Of total 263 out patients interviewed, majority of them reported that the amenities related to infra-structure (47-68%) and OPD timings (96.6%) were satisfactory. However, 32% and 23% of the patients reported that seating facility and waiting time were not satisfactory respectively. Almost all patients were satisfied regarding competency, behaviour of siddha doctors and pharmacists. Of the 217 patients who revisited the siddha wing, most of the patients (98.2%) reported improvement in their illness. There is a scope to improvise the amenities related to infra-structure in these health facilities.